Analysis of Kulin KK LMDH Sumber Lestari Based Agroforestry Social Partnership Program in BKPH Tulungagung - Mardiani Dian; Ahsin Daroini; Supriyono (Faculty of Agriculture, Merdeka University Surabaya, 2021)
Forest Village Community Institution (LMDH)